Review: Restoration, Reformation, and Reform, 1660–1828: Archbishops of Canterbury and Their Diocese - Shaw, Jane (The journal of theological studies, 2005)
Restoration, Reformation, and Reform, 1660–1828: Archbishops of Canterbury and Their Diocese Jeremy Gregory xiii + 355 5 maps. (Oxford Historical Monographs.)Oxford Oxford University Press 2000 0 19 820830 8 £45